THU0601 Cardiovascular screening among patients with inflammatory arthritis: to what extent do patients follow recommendations?. (15th June 2017) - Kjeldgaard, AH; Hørslev-Petersen, K; Christensen, RD; Søndergaard, J; Primdahl, J
Abstract : Background: Patients with inflammatory arthritis (IA) have a substantially increased risk for cardiovascular (CV) disease and consequently regular screening is recommended (1). Objectives: To investigate whether patients with known IA and high CV risk follow the recommendation, given in a nurse-led CV risk screening consultation, to consult General Practice in order to reduce their CV risk. Furthermore to investigate the influence of socioeconomic position and gender. Methods: A register-based cohort study comprising outpatients at King Christian X's Hospital for Rheumatic Diseases, Graasten, Denmark, diagnosed with rheumatoid arthritis (RA), psoriatic arthritis (PsA) or spondylo arthritis (SpA), who had participated in at least one screening consultation based on the EULAR recommendations (1) between 1st of July 2012 and 1st of July 2015. The primary outcome was a consultation with their GP and at least one intervention of relevance for CV risk within 3 months after the screening consultation. Results: 1266 patients, 18–85 years of age, were included; 72.5% with RA and 27.5% with SpA or PsA. Of the 447 (35%) with high risk of CV disease, 60% consulted GP after the screening visit compared to 55% for the 819 patients with low risk of CV disease. Of the 60% of patients with high risk who consulted their GP, 41% had at least one relevant intervention. Education ≥10 years increased the odds for non-compliance (Odds Ratio [Confidence interval]) (0.72 [0.56;0.92], p=0.01) and age above 65 years increased the odds for compliance (1.50 [1.15;1.95], p=0.03). Income, diagnosis, gender, Low Density Lipoprotein level and systolic blood pressure did not significantly influence the odds to consult their GP after the screening consultation. Among high risk patients, 7.4% had their blood glucose checked at a GP consultation and 6.3% had their blood-pressure measured with at-home equipment after the screening consultation as opposed to 4.8% and 1% among low risk patients. Conclusions: After a screening consultation, 40% of the patients with high risk of CV disease did not consult their GP at all in the following 3 months. At least 33% of the patients with high risk followed the recommendations to consult their GP and 27% consulted their GP for reasons not possible to clarify in this study. Only age and higher education had a significant influence on the outcome. References: Peters, M.J., et al., EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis, 2010. 69(2): p. 325–31. Acknowledgements: We would like to thank The Danish Rheumatism Association and the Henrik Henriksens fund for financial support for this study. Disclosure of Interest: None declared